Second‐generation antipsychotic long‐acting injections in bipolar disorder: Systematic review and meta‐analysis. (11th November 2018) - Prajapati, Asta R.; Wilson, Jon; Song, Fujian; Maidment, Ian
Abstract: Background: Non‐adherence is a significant problem in bipolar disorder. Second‐generation antipsychotics (SGA) long‐acting injections (LAIs) may improve adherence in bipolar disorder and may prevent relapses. However, the evidence is limited and conflicting. Objective: The objective of this study was to evaluate efficacy and safety of SGA LAIs in bipolar disorder. Method: Systematic review and meta‐analysis of randomised controlled trials (RCTs) (≥6 months duration) investigating safety and efficacy of SGA LAIs for bipolar disorder. We searched Pubmed, Embase, CINAHL, Cochrane, PsycINFO, LiLACS, www.clinicaltrials.gov up to October 2016. We also contacted the manufacturers of SGA LAIs. Primary efficacy and safety outcomes were relapse rate and all‐cause discontinuation respectively. Results: Total of seven RCTs (n = 1192) were included. SGA LAIs show superiority over placebo for study‐defined relapse rate (RR = 0.58, 95% CI = 0.49‐0.68, P < 0.00001) and all‐cause discontinuation (RR = 0.72, 95% CI = 0.64‐0.82, P < 0.00001). However, no significant difference was found between SGA LAIs and oral active control for relapse rate (RR = 0.92, P = 0.79) and all‐cause discontinuation (RR = 1.2, P = 0.31). In terms of secondary outcomes, SGA LAIs performed better than placebo in relapse to mania/hypomania, young mania rating scales (YMRS), clinical global impression‐severity (CGI‐S), montgomery‐asberg depression rating scale (MADRS). There was no significant difference between SGA LAIs and oral active control regarding relapse to mania/hypomania, YMRS, CGI‐S, extra‐pyramidal side effects (EPSEs), weight gain. However, the active control performed better than SGA LAIs in relapse to depression, MADRS, and prolactin‐related AEs. Conclusions: Current evidence is very limited to support the use of SGA LAIs (compared to oral medication) in bipolar disorder. Further high‐quality studies, particularly comparing SGA LAIs with active control, are warranted.